Multi-Stakeholder Partnership in Nutrition: An Experience from Bangladesh - Kar, Basanta Kumar (Indian Journal of Community Health, 2014)
Context and legitimacy: Bangladesh, a country with 160 million people, is among the 20 countries which have had major accomplishments in reducing child mortality and improving maternal health (Millennium Development Goal 4 and 5 respectively). The government of Bangladesh aims to transition into a middle income country by 2021, and is committed to reduce social discrimination, environmental degradation, physical insecurity, socio-economic-cultural vulnerability and to secure and sustain an annual rate of GDP growth of 10% from 2017.